Pendidikan Akidah Pada Santri Kuttab Al-Firdaus Kota Lhokseumawe - Musyfira, Musyfira (Tadabbur: Jurnal Peradaban Islam, 2021)
The responsibility of religious education is the most important responsibility for parents and educators because it is the center of all resources. However, in practice there are still many educators who do not pay attention to the religious education of their students, they prioritize education that is only worldly. The research method used is qualitative research. Data collected through observation, interviews, and documentation. The data analysis technique used is thematic analysis. The results of this study indicate that the implementation of Islamic education in Kuttab students is going well. Opportunities for the application of Islamic education to Kuttab students starting from the education system, curriculum, and teachers are extraordinary in maximizing education for children. However, it also has challenges that greatly affect children's education, namely gadgets, games, and shows that are not beneficial to children, so it greatly influences the education of their faith. The advantages of the implementation of Islamic education in Kuttab, namely that children have begun to form creeds according to their age. While the drawbacks are that the application and understanding of Islamic education in Kuttab are not comprehensive and agree on all teachers and the environment that does not support the concepts that have been implanted in Kuttab.